ANALYZING ERRORS IN THESIS WRITING: SHOULD GRAMMAR BE AN ISSUE IN ENGLISH ACADEMIC WRITING FOR STUDENTS OF ENGLISH COLLEGE? - Tambunan, Anna Riana Suryanti; Andayani, Widya; Setiasari, Winda; Lubis, Fauziah Khairani; Saragih, Bahagia (Research And Innovation In Language Learning (RILL), 2020)
The result section is an essential part of the thesis to summarize information about research findings. Presenting research findings in terms of clear and concise writing is vital for the English students of the higher education. To this, students should know the linguistic aspects of writing. Previous research shows that a lot of research has been carried out regarding grammatical issues in writing, but little research has been done on deep grammar issues in writing the result section of the thesis. Thus, this study aims to analyze the grammatical issues in student-researchers? thesis. Data were officially collected from the reading room of the faculty of state university in Medan. The data were analyzed according to Bourke & Holbrook's (1992) theory. The results show student-researchers are still struggling to use verb-form issues, nouns, and tenses. At last, word form remains the most dominant issues of errors.